2008
DOI: 10.1111/j.1469-185x.2008.00037.x
|View full text |Cite
|
Sign up to set email alerts
|

An integrative view of sexual selection in Tribolium flour beetles

Abstract: Sexual selection is a major force driving the evolution of diverse reproductive traits. This evolutionary process is based on individual reproductive advantages that arise either through intrasexual competition or through intersexual choice and conflict. While classical studies of sexual selection focused mainly on differences in male mating success, more recent work has focused on the differences in paternity share that may arise through sperm competition or cryptic female choice whenever females mate with mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
118
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(122 citation statements)
references
References 155 publications
1
118
0
Order By: Relevance
“…Attractiveness is frequently positively associated with courtship in insects, including flour beetles [7,[47][48][49][50]. Thus, we measured courtship rate (CR: number of courtship bouts per second, during a single successful courtship period) as a measure of courtship quality [7,46].…”
Section: Methodsmentioning
confidence: 99%
“…Attractiveness is frequently positively associated with courtship in insects, including flour beetles [7,[47][48][49][50]. Thus, we measured courtship rate (CR: number of courtship bouts per second, during a single successful courtship period) as a measure of courtship quality [7,46].…”
Section: Methodsmentioning
confidence: 99%
“…Sperm storage often occurs in animals that have copulations with multiple males ('multiple paternity'), where the combination can create selective advantages (e.g. Vonhof et al, 2006;Fedina and Lewis, 2008;Griffiths et al, 2012). Indeed, in some species, fertile eggs of different ages fathered by different males can coexist in a female's oviduct.…”
Section: Reviewmentioning
confidence: 99%
“…This correlation between antipredator behaviour and general activity could potentially result in a trade-off between survival under predatory conditions and mating success under predator-free conditions. General activity when encountering mates is likely to be particularly important in species such as the flour beetle (Fedina & Lewis 2008), which does not exhibit male -male competition or male courtship before mating. To our knowledge, however, no empirical study has identified a genetic basis to such a trade-off, by actually comparing survival rates and mating success rates using individuals that exhibit different behavioural tendencies.…”
mentioning
confidence: 99%